2008
DOI: 10.1093/humrep/dem432
|View full text |Cite
|
Sign up to set email alerts
|

17- -Estradiol in relation to age at menarche and adult obesity in premenopausal women

Abstract: Our findings support the hypothesis that early age at menarche, together with adult overweight and obesity, result in high levels of 17-beta-estradiol throughout the menstrual cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 46 publications
8
69
0
1
Order By: Relevance
“…Two women were excluded, due to missing mammographic data, leaving data from 202 premenopausal women available for the present study. Validated and standardized questionnaires (self-and interviewer-administered by trained personnel) were used to collect information about reproductive history, previous hormone use, diet, and lifestyle habits (21,28,31).…”
Section: Participants and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Two women were excluded, due to missing mammographic data, leaving data from 202 premenopausal women available for the present study. Validated and standardized questionnaires (self-and interviewer-administered by trained personnel) were used to collect information about reproductive history, previous hormone use, diet, and lifestyle habits (21,28,31).…”
Section: Participants and Study Designmentioning
confidence: 99%
“…However, it is less known whether HDL-C, is associated with mammographic density, in particular for premenopausal women (26,27). We have previously studied the association between cyclic estrogen and an unfavorable metabolic profile (21,28), and observed that HDL-C was inversely associated with cyclic estrogen (21). The complexity of assessing cyclic hormones throughout an entire menstrual cycle among premenopausal women underlines the importance of inclusion of both total serum levels (bound) and direct measurements of unbound levels of salivary hormones.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 17β-estradiol profiles were associated with traditional breast cancer risk factors, such as age at menarche [19,20], insulin, adult height and metabolic profile in adulthood [21,19,22]. These associations also point to the need for further studies of estrogen in combination with the GH-IGF signalling pathway and mammographic density.…”
Section: Introductionmentioning
confidence: 99%
“…Age at menarche tends to occur earlier, especially in those with decreasing birth weight who gain more weight during pre-pubertal years (5), (13), (15). Interestingly, we recently observed that women who experienced early age at menarche (#12 years) and had a large waist to hip ratio, had 24% higher levels of estradiol over the menstrual cycle (16).…”
Section: Introductionmentioning
confidence: 99%